2011
DOI: 10.1039/c0jm02246b
|View full text |Cite
|
Sign up to set email alerts
|

Viability of plant spore exine capsules for microencapsulation

Abstract: Sporopollenin exine capsules (SECs) (outer exoskeletal wall of the spores of Lycopodium clavatum) were extracted and examined for their potential use as microcapsules. They were shown, by laser scanning confocal microscopy (LSCM), to be void of their inner contents. The removal of nitrogenous and other internal materials was supported by a combination of elemental and gravimetric analyses. Two different methods were investigated to encapsulate substances into SECs which were (i) mild passive migration of mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
119
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(130 citation statements)
references
References 33 publications
10
119
1
Order By: Relevance
“…Figs 3D, 3E, 3F, 3G, and 3H show treated LSs that are filled with sulforhodamine (558 Da), dextran (4 kDa), OVA (45 kDa), bovine serum albumin (67 kDa), and dextran (2000 kDa), respectively. This result is consistent with a recent study that successfully encapsulated oils, fats and proteins such as β-galactosidase (540 kDa) and horseradish peroxidase (100 kDa) in LSs [23]. Thus, a wide range of molecules can be filled in to LS core demonstrating the flexibility of the platform for vaccine delivery.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Figs 3D, 3E, 3F, 3G, and 3H show treated LSs that are filled with sulforhodamine (558 Da), dextran (4 kDa), OVA (45 kDa), bovine serum albumin (67 kDa), and dextran (2000 kDa), respectively. This result is consistent with a recent study that successfully encapsulated oils, fats and proteins such as β-galactosidase (540 kDa) and horseradish peroxidase (100 kDa) in LSs [23]. Thus, a wide range of molecules can be filled in to LS core demonstrating the flexibility of the platform for vaccine delivery.…”
Section: Resultssupporting
confidence: 91%
“…Indeed, using this conceptual framework LSs have recently been proposed for oral drug delivery. It has been shown that proteins as large as 540 kDa, a magnetic resonance imaging contrast agent, food oils including cod liver oil can be filled into LSs [19-23]. While these in vitro studies demonstrate the flexibility of filling LSs with different molecules, in vivo demonstrations on the effectiveness of pollens for oral drug and vaccine delivery are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…This study also described the encapsulation of polar materials, such as enzymes (amylase, galactosidase, alkaline phosphatase and sHRP (horseradish peroxidase)) with loading around 20% (drug:drug and exine) but most significantly these experiments showed that the enzymes kept most of their catalytic activity when they were re-extracted from the shells [62]. …”
Section: Encapsulation and Release Of An Activementioning
confidence: 99%
“…Examples of this technique can be found in studies by Barrier et al , including encapsulating a solution of alkaline phosphatase in glycerol at 4 °C with a 20% loading [62]. …”
Section: Encapsulation and Release Of An Activementioning
confidence: 99%
“…[ 14 ] Recent studies have demonstrated the use of processed L. clavatum shells for encapsulation, [15][16][17][18][19] however, the production of L. clavatum sporopollenin capsules requires the prolonged processing of natural spores with harsh chemical treatments at elevated temperatures, so as to isolate the sporopollenin exine shell. [20][21][22][23][24] In many applications, this extensive processing may be unnecessary and potential therapeutic benefi ts may be lost. For applications in medicine, cosmetics, and food, enhanced effects may be obtained through the encapsulation of synergistic compounds, [ 25 ] and overall, the use of natural unprocessed spores provides signifi cant benefi ts in terms of processing complexity and costs for a wide range of applications.…”
Section: Introductionmentioning
confidence: 99%